INVENTARISASI HAMA AKIBAT PERLAKUAN MACAM JARAK TANAM TERHADAP TIGA VARIETAS KEDELAI Glycine max (L) Merill - Lulus Fitriyani; Sartono Joko Santosa; Sumarmi Sumarmi (Innofarm:Jurnal Inovasi Pertanian, 2019)
The purpose of this research was to investory the types of pest from the symptoms and signs of damage from variouse types of planting distance on there of soybean. This research was conducted in April 2019 until Juli 2019, a research site in Gatak Hamlet, Senting Village, Sambi Subdistrict, Boyolalai Regency with Grumosol soil types and altitude ± 200 meters above sea level. This study uses a Complete Randomized Block Design (CRBD) arranged in Split Plots consisting of 2 treatment factors, namely the type of soybean (V) as the main plot an planting distance (J) as a sub plot, so 9 treatment combinations were obtained and each was repeated 3 times. The results showed (1) The types of pest found at the time of the study were green grasshopper pest with the highest attack intensity in the treatment Grobogan of varieties  with planting distance 30 cm x 40 cm (V1J3), wich was an average 0f 29.79%. Caterpillar leaves pest with the highest attack intensity in the treatment Grobogan of varieties with planting distance 30 cm x 40 cm (V1J3), wich was an average 0f 30%, Anjasmoro of varieties with planting distance 30 cm x 20 cm (V2J1), wich was an average 0f 30%, Grobogan of varieties with planting distance 30 cm x 30 cm (V2J2), wich was an average of 30%. Pod borer pest with the highest attack intensity in the treatment Anjasmoro of varieties with planting distance 30 cm x 30 cm wich was an average of 29,97% (2) The provision of spasing 30 cm x 40 cm does  significantly affect the intensity of pest attacks on three types of soybean (3) Grobogan of varieties and spasing 30 cm x 40 cm (V1J3) had the highest the number of pods yields which was an average of 88 pods, the pod weight 60,11 gram/m2, and yield of seed weight 16,95 gram/m2. And the highest the number of seeds yields had the highest on Grobogan of varieties and spasing 30 cm x 40 cm which was an average 143,56 seeds, and on Grobogan varieties  with planting distance 30 cm x 30 cm of was an average 13,60 gram/m2.